Guanyem la llibertat : la resposta socialista / [Partit Socialista de Catalunya]
En port: Parlaran: J. Andreu Abelló, Anna Balletbò, M° Aurèlia Capmany, Alexandre Cirici, Joan Colomines, J.J. Ferreiro, Elies Lopez Blanco, Jordi Llimona, Joan Reventós, Josep VidalEn la cub.: P.S.C.: el míting de la llibertat